Charting climate adaptation integration in smart building rating systems: a comparative study - Khoja, Ahmed; Danylenko, Olena (Frontiers in Built Environment, 2024)
As the world is engulfed with the growing impacts of climate change, the integration of climate adaptation measures into building performance requirements is essential. In the era of the 4th industrial revolution, smart buildings are expected to be the next frontier in the realm of building rating systems after sustainability-based one. Smart buildings can play a pivotal role in addressing the evolving challenges of changing climate due to their temporal and spatial cross-scale nature.Methods: This study assesses the integration of climate hazard adaptation options within four prominent smart building rating systems (SBRS). Using a sectoral analysis approach and a 4-point Likert scale, we systematically evaluate the extent to which these rating systems incorporate climate adaptation measures directly or indirectly across multiple building sectors. We identify strengths and weaknesses in each system's approach, highlighting areas where adaptation options are more profoundly addressed and sectors that require further attention.The evaluation results reveal variations in the comprehensiveness of climate adaptation integration among the smart building rating systems. The SRBS show a high level of integration of climate adaptation measures in the urban sectors intrinsically tied to the smart building paradigm, such as communication sector, and the human wellbeing and organization sector. Nevertheless, the study also revealed that SBRS almost universally fall short in covering other vital domains such as building envelope and structure, water and sanitation, and blue and green infrastructure.Discussions: Complementing the SBRS with sustainability rating systems (GBRS) can effectively address the limitations in climate adaptation integration within SBRS. Moreover, the inherent interconnectedness of smart buildings with their surrounding infrastructure and the broader urban environment underscores the importance of the cross-scale consideration in the building rating domain in general and in climate related topics in particular, this interconnectedness also highlights a smart building's reliance on its surrounding context for optimal functionality and the interdependency between the building and urban scale.